Pengaruh Perputaran Piutang dan Perputaran Modal Kerja terhadap Profitabilitas - Luthfiyyah Muhadzdzab; Herlina Rasjid; Raflin Hinelo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aim to determine the effect of Receivables Turnover and Working Capital Turnover on Profitability in General Insurance Companies Listed on the Indonesia Stock Exchange from 2019 to 2023. The sampling technique for this research is purposive sampling, and the number of samples consists of 9 banking companies. The data collection technique in this research uses secondary data from financial statement data published by General Insurance Companies Listed on the Indonesia Stock Exchange (IDX). The data analysis uses multiple linear regression analiysis, and the data analysis method uses the SPSS 23 application. The test result using multiple linear regression shows that, partially, working capital turnover contributed to a negative and significant effect on profitability, meaning that the increase and decrease in working capital do not affect the profits received by the company. Receivables Tunover hand a positive and significant effect on profitability. Simultan eously, Accounts Receivables Turnover and Working Capital Trunover effected Profitability General Insurance Companies.